2011
DOI: 10.1089/sur.2010.073
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Regimen and the Timing of Prophylaxis Are Important for Reducing Surgical Site Infection after Elective Abdominal Colorectal Surgery

Abstract: Appropriate antibiotic selection and timing of administration for prophylaxis are crucial to reduce the likelihood of SSI after elective colorectal surgery with intestinal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 27 publications
0
53
0
4
Order By: Relevance
“…All studies were observational; no randomized controlled trials (RCT) were found. Of the observational studies, 1 was a case control study, [16] 2 were retrospective cohorts, [17,18] and 11 were prospective cohorts. [46,19–26] Most studies included a variety of surgical procedures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were observational; no randomized controlled trials (RCT) were found. Of the observational studies, 1 was a case control study, [16] 2 were retrospective cohorts, [17,18] and 11 were prospective cohorts. [46,19–26] Most studies included a variety of surgical procedures.…”
Section: Resultsmentioning
confidence: 99%
“…[5,6,1618,2123,25] Nine studies reported postoperative antibiotic continuation with a varying duration up to 48 hours. [46,17,18,2123,27] Five studies did not report on postoperative antibiotic regimen. [16,19,20,25,26] Four studies reported a re-dosing regimen within 4 hours after first administration, [6,17,25,26] 3 studies reported a procedure duration not requiring re-dosing, [20,22,23] 7 studies reported no information on re-dosing.…”
Section: Resultsmentioning
confidence: 99%
“…No antibiotics are recommended for uncomplicated clean surgery [11,12]. Ho et al 2011 emphasized the importance of appropriate antibiotic choice in elective colorectal surgery as she found a statistically significant increase in SSI when nonstandard regimens were administered (odds ratio 2.069; 95% confidence interval 1.078e1.868) [29].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies of treatment of infections with CRE have looked at a heterogeneous mix of organisms and patients, and carbapenem containing regimens have been shown to confer a mortality benefit in the context of a MIC that is not conspicuously resistant. 195 196 Extended infusion regimens may restore efficacy even when the in vitro MIC is slightly above the resistance breakpoint, 197 and dual carbapenem therapy may be considered for KPC producing Enterobacteriaceae using ertapenem as an additional (sacrificial) substrate to saturate or overwhelm the capacity of the KPC enzyme to hydrolyze the principal therapeutic carbapenem. [198][199][200] The benefits of dual β lactam therapy warrant review, 201 whether they accrue from synergistic action at a single target site or from targeting different penicillin binding proteins (as for enterococcal therapy with ampicillin and cefotaxime or ceftriaxone).…”
Section: Emerging Treatmentsmentioning
confidence: 99%